Institutions, Economic Development, and Deforestation - Michael Grimm; Stephan Klasen; Stefan Schwarze (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
This paper offers a unified framework linking two important debates: First, the debate about the respective roles of geography and institutions on economic development; Second, the literature on the role of technological change and economic development on agricultural intensification and land use changes. We use this framework to study empirically deforestation patterns at the rainforest margin. To this end we specify an empirical model that can explore the causal chain ranging from geographic conditions via institutional change to economic development and deforestation. We estimate this model using a unique data set of villages at the rainforest margin in Indonesia. Our results show that geography-induced institutional change is the key driver of technological change in our villages. The bad news is that some of these processes along the causal chain seem to promote deforestation. The good news is that economic development, conditional on these effects, appears to reduce deforestation.
Keywords: O1; Q2; 330